2023
DOI: 10.1111/ffe.14033
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the effect of surface microgeometry and residual stress on conformal contact fretting fatigue crack initiation behavior

Abstract: Conformal contact is a commonly presented contact form in assemblies. Nonproportional loading is the main characteristics of conformal contact, which leads to prominent difficulty in revealing fretting crack behavior. In this paper, a finite element prediction model for Ti-6Al-4V pin-hole contact fretting fatigue crack initiation was developed, which simultaneously considered the effect of fretting wear, surface roughness, surface skewness, surface kurtosis, and residual stress. The results show that phase dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Maz anov a et al 10 revealed that microstructure also has a significant impact on the multiaxial fatigue behavior of materials. Our previous works [11][12][13] correlated surface roughness parameters such as skewness, kurtosis, and texture direction with fatigue life. These studies indicate that surface integrity, including residual stress, microstructure, and surface roughness, has a significant influence on the surface fatigue performance of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Maz anov a et al 10 revealed that microstructure also has a significant impact on the multiaxial fatigue behavior of materials. Our previous works [11][12][13] correlated surface roughness parameters such as skewness, kurtosis, and texture direction with fatigue life. These studies indicate that surface integrity, including residual stress, microstructure, and surface roughness, has a significant influence on the surface fatigue performance of materials.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the loading protocol, the influences of out-of-phase loading [10] and phase difference ( [11,12]) (however, mainly with focus on a phase difference between bulk stresses and contact loads), as well as more complex cyclic loading paths ( [13,14]), were studied. On the other hand, regarding the influence of the surface geometry on crack initiation, the overall contact geometry ( [15,16]) and macroscopically worn profiles [17], as well as the surface microgeometry [18], surface pit treatment [19] and machined surface texture [20] have been considered. Most of the aforementioned numerical studies are based on the Finite-Element Method (FEM); while the FEM, due to its flexibility with respect to the physical modeling, can account for a wide variety of mechanisms and phenomena in a specific fretting contact-and thus achieves good predictive power under sufficiently well-defined circumstances-its demands for computational power and calculation time often make large parameter studies for the comprehensive analysis of different influencing factors unfeasible.…”
Section: Introductionmentioning
confidence: 99%